Trainees’ Perception on the CBET Curriculum in Kenya: The Case of TVET Institutions in Coast Region - Mwashighadi, P. Mwagunga; Kerre, B. Wanjala; Kitainge, Kisilu (African Journal of Education,Science and Technology (AJEST), 2020)
A considerable number of Technical and Vocational Education and Training (TVET) trainees released for the market are characterized by incompetence as they cannot exhibit behavior commensurate with the aspects of learning acquired at their different levels. Additionally, results from Southern Africa Consortium of Monitoring Educational Quality (SACMEQ-III) show that Kenya’s basic education system is failing to produce graduates with skills and competencies that satisfy the needs of a participatory society and the knowledge economy. Using this situation as a rationale, this study sought to find the reasons behind incompetence of trainees and the challenges faced by trainers in implementing competency-based programs in TVET institutions in Coast region. Three public TVET institutions in Coast region were considered in this study. To achieve this purpose, the following research questions were adopted, ‘what is the trainers understanding of the concept and objectives of Competence Based education and Training (CBET) curriculum?’, ‘how do trainer’s involve students in classroom activities?’, ‘ to what extent are the training institutions, trainers and their trainees attached to industries and other business sectors?’, ‘are teaching/learning materials and equipment available for the training of CBET?’, and ‘what is the perception of trainees towards CBET curriculum?’. Descriptive research method was employed to collect information from respondents. The target population was 870 and the sample size was 136; comprising of 22 trainers’, 94 trainees, 3 principals, 3 Industrial Liaison Officers, and 18 Heads of Department. Purposive sampling was used to select the TVET institutions and stratified random sampling was used to select the respondents. All the Principals, Heads of Department and Industrial Liaison Officers were used in the study as their population was not large. Instruments of data collection involved Questionnaires, Interview guides and observations checklist. Data from completed instruments were coded and analyzed using SPSS. Frequency tables, Percentages and chi square were used to analyze the data. The study found that trainers had good understanding of the concept and objectives of CBET Curriculum. Based on these findings it is recommended that, the government should support TVET institutions in hiring of more qualified trainers and technical support staff; stakeholders, that is, parents, industries, government and donors should contribute to providing adequate training equipment that are technologically modern in order to equip the training workshops. Further, government should use different options like tax reduction, rewarding and providing incentives to participating companies to motivate industry owners and micro and small enterprises to cooperate fully with TVET institutions to support training.